ANALISIS KERJASAMA PROGRAM STUDI BKPI UNTUK MEWUJUDKAN PROYEK INDEPENDEN MAHASISWA PADA MERDEKA BELAJAR KAMPUS MERDEKA - Fadila; Febriansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms of collaboration implemented by the Islamic Educational Guidance and Counseling Study Program (BKPI) in realizing independent student projects and to examine partner institutions’ perceptions regarding the opportunities and challenges faced by the BKPI Study Program. This research employed a mixed-methods approach, integrating qualitative and quantitative methods. The qualitative approach was used to explore the forms of collaboration and to analyze partner institutions’ perceptions of opportunities and challenges in implementing independent student projects. The quantitative approach was applied to measure the level of collaboration conducted by the BKPI Study Program in supporting independent student projects. Primary data were obtained from BKPI lecturers and students, while secondary data were collected from faculty leaders and institutional administrators. Data collection techniques included questionnaires, observations, interviews, and documentation. Qualitative data were analyzed inductively, while quantitative data were analyzed using percentage analysis. The results indicate that collaboration between the BKPI Study Program and schools in implementing independent student projects includes field practice, research activities, and field studies. Collaboration through field practice received 77 percent “strongly agree” and 20 percent “agree” responses. Collaboration through research obtained 70 percent “strongly agree” and 27 percent “agree.” Collaboration through field studies achieved 71 percent “strongly agree” and 28 percent “agree.” Partner institutions perceive that the BKPI Study Program has strong opportunities to realize independent student projects through employment prospects, the transfer of theoretical knowledge into professional practice, and exposure to clients from diverse cultural backgrounds. However, several challenges were identified, including the complexity of clients’ problems and the need for counselors to apply educational theories carefully within counseling practices to ensure professionalism, effectiveness, and ethical responsibility in diverse educational and social settings.